All-organic microelectromechanical systems integrating electrostrictive nanocomposite for mechanical energy harvesting. (February 2018) - Nesser, Hussein; Debéda, Hélène; Yuan, Jinkai; Colin, Annie; Poulin, Philippe; Dufour, Isabelle; Ayela, Cédric
Abstract: Recent advances in the field of microelectromechanical systems (MEMS) have generated great interest in the substitution of inorganic microcantilevers by organic ones, due to their low cost, high flexibility and a simplified fabrication by means of printing methods. Here, we present the integration of electrostrictive nanocomposites into organic microcantilever resonators specifically designed for mechanical energy harvesting from ambient vibrations. Strain sensitive nanocomposite materials composed of reduced graphene oxide (rGO) dispersed in polydimethylsiloxane (PDMS) are integrated into all-organic MEMS by means of an innovative low-cost and environment friendly process by combining printing techniques and xurography. Static tests of the electrostrictive nanocomposite with 3.7 wt% rGO show good performances with variations of capacitance that exceeds 4% for strain values lower than 0.55% as the microcantilever is bent. The results in dynamic mode suggest that the organic MEMS meet the requirements for vibration energy harvesting. With an applied sinusoidal acceleration (amplitude 0.5 g, frequency 15 Hz) a power density of 6 μW/cm 3 is achieved using a primitive circuit. Graphical abstract: Highlights: Innovative and environmental friendly process of electrostrictive MEMS resonators. All-organic electrostrictive MEMS with excellent mechano-electrical performances. Integrated microgenerators specifically designed for mechanical energy harvesting. Versatile MEMS design for future applications in mechanical energy harvesting.